Strategies to Increase Social Awareness as a Form of Conflict Resolution in the Kei Islands Community - Ufie, Agustinus; Syamsu A. Kamaruddin,; A. Octamaya Tenri Awaru,; Arlin Adam, (Technium Social Sciences Journal, 2024)
Social awareness is a very important thing and must be possessed by the community in dealing with conflicts in society. The purpose of this study is to analyze the strategy of analyzing social awareness as a form of conflict resolution in the Kei community. Meanwhile, the method used in this study is qualitative with a phenomenological approach. Data were collected through observation and interviews. The data obtained was analyzed in three stages, namely reduction, data presentation and conclusion drawn. The results of the study show that strategies to increase social awareness as a form of conflict resolution in the Kei community include (a) Education in the family, (b) Promotion of Local Culture, (c) Women’s Empowerment, (d) Joint Activities. The findings can be used as a reference for stakeholders in designing programs and supporting social harmony and emphasizing the values of brotherhood, collective participation and effective communication in society.